Phylogenetic Analysis of Araucariaceae: Integrating Molecules, Morphology, and Fossils - Escapa, Ignacio Hernan (2013)
Premise of research: Phylogenetic relationships of Araucariaceae (Coniferophyta, Araucariales) are revised on the basis of the first combined data matrix for the family. Methodology: Taxon sampling includes 39 ingroup species (31 extant, 8 fossils) and outgroup species of all the remaining conifer families. Five fossil Araucaria species, one species of the genus Araucarites, and two species of the extinct genera Wairarapaia and Emwadea were included in the analyses. Character sampling includes 23 genomic regions (19 plastid, 2 nuclear, and 2 mitochondrial) and 62 morphological characters (52 discrete and 10 continuous). The phylogenetic analyses were conducted with equally weighted parsimony. Additionally, several analyses under different taxon- and gene-sampling regimes were analyzed for identifying the causes of the long-lasting controversies in the interrelationships of the three extant genera of Araucariaceeae. Pivotal results: Monophyletic Araucariaceae is the sister group of Podocarpaceae, forming the order Araucariales. Monophyly of Araucaria and Agathis is also strongly supported by the data. The results of both molecular and combined analyses indicate that Wollemia and Agathis form a clade (=agathioid clade) sister to Araucaria. Within Araucaria, the analyses support the monophyly of the four currently recognized sections: Araucaria, Bunya, Intermedia, and Eutacta. Results support the monophyly of living and fossil Araucaria (including Araucarites), whereas the remaining extinct genera are placed as the stem of the agathioid clade. In terms of the sensitivity analyses performed, results suggest that inconsistencies among previous results would be related to ingroup sampling. Conclusions: By means of a combined phylogenetic analysis, we have been able to obtain a strongly supported and well-resolved phylogeny of Araucariaceae that includes both living species and fossil species for the group. This study shows the feasibility and usefulness of phylogenetic analyses that incorporate multiple sources of evidence (molecules/morphology, living/fossil species, discrete/continuous characters).